1994
DOI: 10.1055/s-2007-994574
|View full text |Cite
|
Sign up to set email alerts
|

Brain Temperature Discriminates Between Neonates with Damaged, Hypoperfused, and Normal Brains

Abstract: Brain temperature depends on the balance of cerebral heat production and heat loss via cerebral circulation and head surface. We investigated whether brain temperature and heat loss via the head surface differed in neonates with abnormal cerebral metabolism or circulation. We measured the core temperature of the head noninvasively by the zero-gradient method, skin temperature of the head, the heat flux from the head, and esophageal and operative environmental temperature in seven healthy neonates, seven neonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…Infant studies have reported T rec $ 0.58C greater than abdominal skin temperature (35) and head core temperature approximately 0.78C greater than oesophageal temperature (36). In our study, infant abdominal skin temperature was 36.5-37.58C, suggesting a head core temperature approximately 1.08C higher and compatible with T AWC .…”
Section: Comparative Brain Mrstsupporting
confidence: 56%
“…Infant studies have reported T rec $ 0.58C greater than abdominal skin temperature (35) and head core temperature approximately 0.78C greater than oesophageal temperature (36). In our study, infant abdominal skin temperature was 36.5-37.58C, suggesting a head core temperature approximately 1.08C higher and compatible with T AWC .…”
Section: Comparative Brain Mrstsupporting
confidence: 56%
“…In small animals the temperature beneath the temporalis muscle has been found to closely reflect the brain core temperature. In two human newborns with external drainage the temperature gradient between the intraventricular space and the head skin has been found to differ less than 1.5 C [5]. Consequently it seems justified to use epidural temperature as a measure of changes in brain temperature for comparing various other body temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…itored indirectly by means of nasopharyngeal temperature (T nasoph ) differs from other body core temperatures with considerable differences in the presence of various diseases [4,5] and induced hypothermia [6,7]. Apart from highly sophisticated techniques such as magnetic resonance spectroscopy [8] and microwave thermography [9], temperature measurements at the tympanic membrane [10], meatus accusticus [11], insulated temple [12], forehead [5,13], nasopharynx [14], esophagus (T esoph ), bladder, and rectum (T rectum ) [15] have been proposed for the noninvasive monitoring of a temperature analogue of the brain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A full characterisation of the phenomenon would require the use of calorimetry to quantify the heat transfer to the environment. The greatest challenge is to identify a relationship between thermal maladaptation and encephalopathy following HI delivery [37]. …”
Section: Figmentioning
confidence: 99%